The practice of applying a system-activity approach in teaching Russian to students of foreign language groups at a university - Grigoreva, Marina Igorevna (The Lingua Spectrum, 2026)
The article is devoted to the issues of practical application of the system-activity approach in teaching Russian to students of foreign language groups in higher education. The relevance of the study is determined by the need to improve the methodology of teaching Russian as a second language, aimed at the formation of communicative competence, the development of critical thinking, cognitive independence and the ability of students to effectively use the language in educational, professional and everyday activities. The theoretical foundations of critical thinking are examined and opportunities for its implementation in Russian language learning are explored through the organization of active cognitive and verbal activities among students. Particular attention is paid to the use of interactive methods and techniques, including the “Idea Basket,” “True and False Statements,” “Insert,” and the Case Method. Based on practical experience, it has been shown that the use of a system-activity approach contributes to increased learning motivation, activation of thinking and speech activity, development of analytical abilities, the ability to work with information, to reasonably express one's own point of view and interact in the process of solving communication problems.